2020
DOI: 10.1080/0309877x.2020.1753179
|View full text |Cite
|
Sign up to set email alerts
|

Working smart: the use of ‘cognitive enhancers’ by UK university students

Abstract: Working smart: the use of 'cognitive enhancers' by UK University students Cognitive enhancers include a wide range of substances including prescription medication for attentional deficient disorders and pharmacological substances for cognitive augmentation. Students have recently been identified as the largest cohort of users. Most research on student use of cognitive enhancers has been undertaken in the United States. This study utilised a mixed methods sequential explanatory approach to investigate cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 43 publications
5
24
0
Order By: Relevance
“…Males were here identified as the most typical CE misusers [ 7 , 22 , 30 , 31 , 41 , 51 , 52 , 63 , 66 , 70 , 71 , 73 , 74 , 75 ], with some studies reporting a male:female ratio of 3:1 [ 54 ]. In contrast with this, a Welsh study reported that female representation was slightly more than males [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Males were here identified as the most typical CE misusers [ 7 , 22 , 30 , 31 , 41 , 51 , 52 , 63 , 66 , 70 , 71 , 73 , 74 , 75 ], with some studies reporting a male:female ratio of 3:1 [ 54 ]. In contrast with this, a Welsh study reported that female representation was slightly more than males [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…In another study, 75.5% of methylphenidate was identified as having been purchased from friends at a university campus whilst 64.3% of modafinil was obtained online [ 22 ]. Accessing the web for drug acquisition activities is a reason for concern [ 30 ], with young people (18–25 years old) being at high risk because there is no way to know what the actual ingredients of the drugs/substances are in those products [ 30 ], they are extensive users of the Internet [ 112 ]; it was found that over a third of the websites selling modafinil specifically recommended use of the drug to aid studying [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations